(untitled) (Contemporary Mathematics, 2024)
We introduce a new subclass of starlike functions, denoted by , that are influenced by the Janowski functions, which are well-known in the literature. Our main results are the coefficient estimates of the inverse function and the Fekete-Szegö inequality for this subclass. We also present some special cases of our results that are of interest.